Survival and predictors among preterm neonates admitted at University of Gondar comprehensive specialized hospital neonatal intensive care unit, Northwest Ethiopia - Ayenew Engida Yismaw; Abebaw Addis Gelagay; Malede Mequanent Sisay (BMC, 2019)
Abstract Background Prematurity accounts about 1 million neonatal deaths worldwide and the second causes of both neonatal and under five-child mortality. Neonatal mortality accounts for 43% of under-five child mortality in Ethiopia. From this preterm is the second leading cause of death and is steadily increased in low-income countries. Therefore, the aim of this study was to assess time to death and predictors among preterm neonates admitted in University of Gondar comprehensive specialized hospital neonatal intensive care unit North West Ethiopia 2018. Methods Institution-based retrospective follow-up study was conducted among 516 preterm neonates from January 2016 to March 2018. Data were extracted retrospectively from patients' records using a pretested structured checklist. Descriptive summary statistics like median survival time, Kaplan Meier failure estimation curve and Log-rank test were computed. Bivariate and multivariable Gompertz parametric hazards models were fitted to identify the predictors of mortality. Hazard ratio with a 95% confidence interval was calculated and p-values < 0.05 were considered statistically significant. Results The proportion of preterm neonatal death in this study was 28.8% (95%CI (25.1, 32.9)). Home delivery (AHR = 2.25, 95% CI (1.03, 4.88)), hyaline membrane disease (AHR =3.21, 95% CI (1.96, 5.25)), gestational age, (AHR = 0.82, 95% CI (0.74, 0.91)), cry immediately at birth (AHR = 1.74, 95% CI (1.19, 2.53)), kangaroo mother care (AHR = 0.24, 95%CI (0.11, 0.52)), presence of jaundice (AHR = 1.62, 95%CI (1.12, 2.54)) and hypoglycemia at admission (AHR = 1.75, 95%CI (1.21, 2.54)) were found to be significant predictors of time to death for preterm neonates. Conclusion Proportion of preterm neonatal death in this study was high. Home delivery, Jaundice, hypoglycemia, gestational age, cry immediately at birth, kangaroo mother care and hyaline membrane disease were significant predictors of time to death.